Analisis Kemampuan Pengajuan Soal Calon Guru Sekolah Dasar Ditinjau dari Tingkat Disposisi Matematis - Men, Fulgensius Efrem; Mandur, Kanisius; Jelatu, Silfanus (JOURNAL OF SONGKE MATH, 2018)
Problem-posing ability is the ability to make and solve math problems. This research is qualitative research that aims to describe the ability to submit questions about prospective elementary school teachers concerning mathematical disposition. The subject of this research is the students of prospective school level teachers in the 6th semester, amounting to 3 people. The results of this study are (1) prospective primary school teachers with a high mathematical disposition can submit questions based on the information given related to addition and subtraction of ordinary and mixed fractions, the problem presented are in accordance material with moderate difficulty level, able to solve the problems posed with using a good language structure, (2) prospective primary school teacher with a moderate mathematical disposition level can form a story question based on additional information and subtraction of ordinary fractions, the questions submitted are in accordance material with a relatively low difficulty level and using a good language structure. However, unable to solve the problems raised, and (3) prospective primary school teachers with a low mathematical disposition level are not able to ask questions based on the two information provided. The prospective teacher has difficulty making a story question. These conditions have an impact on not fulfilling several other criteria, among others, conformity with the material, answers to the problems raised, language structure and the difficulty level of the question. The results of the study provide recommendations for policymakers on campus to help prospective students of elementary school teachers to develop problem-posing ability according to the level of mathematical disposition.